Effect of Glutaraldehyde Concentration on Catalytic Efficacy of Candida rugosa Lipase Immobilized onto Silica from Oil Palm Leaves - Emmanuel Onoja; Roswanira Abdul Wahab (Universitas Gadjah Mada, 2019)
Till date, studies that investigated the effect of glutaraldehyde concentration on catalytic efficacy of biocatalyst developed with silica-derived from oil palm leaves (OPL) as support, are unknown. The study presents the preparation of a support consisting of silica extracted from OPL coated over magnetite (G/A/SiO2-M) for the immobilization of Candida rugosa lipase (CRL). Herein, the effect of glutaraldehyde concentration on the catalytic efficacy of immobilized CRL was assessed by the enzymatic production of butyl butyrate as a model. Fourier transform infrared (FTIR) spectra and immobilization parameters indicated that covalent bound CRL on functionalized OPL-derived silica-magnetite composite activated with 4% (v/v) glutaraldehyde solution (100 mM, pH 7.0) (CRL/G/A/SiO2-M) and pretreated in toluene, resulted in a protein loading and an immobilization yield of 68.3 mg/g and 74.3%, respectively. The resultant CRL/G/A/SiO2-M biocatalyst which specific activity was 61.9 U/g catalyzed the esterification production of 76.5% butyl butyrate in just 3 h, as confirmed by analyses of the purified ester using FTIR and 1H NMR spectroscopy. Hence, the finding envisages the promising use of G/A/SiO2-M support fabricated from discarded OPL as a carrier for immobilization and activation of CRL, in conjunction to being a good alternative source of renewable silica.